Self-Timed Scheduling Analysis for Real-Time Applications. (14th June 2007) - Moreira Moreira, Orlando M. Orlando M.; Bekooij Bekooij, Marco J. G. Marco J. G.
Abstract : This paper deals with the scheduling analysis of hard real-time streaming applications. These applications are mapped onto a heterogeneous multiprocessor system-on-chip (MPSoC), where we must jointly meet the timing requirements of several jobs. Each job is independently activated and processes streams at its own rate. The dynamic starting and stopping of jobs necessitates the usage of self-timed schedules (STSs). By modeling job implementations using multirate data flow (MRDF) graph semantics, real-time analysis can be performed. Traditionally, temporal analysis of STSs for MRDF graphs only aims at evaluating the average throughput. It does not cope well with latency, and it does not take into account the temporal behavior during the initial transient phase. In this paper, we establish an important property of STSs: the initiation times of actors in an STS are bounded by the initiation times of the same actors in any static periodic schedule of the same job; based on this property, we show how to guarantee strictly periodic behavior of a task within a self-timed implementation; then, we provide useful bounds on maximum latency for jobs with periodic, sporadic, and bursty sources, as well as a technique to check latency requirements. We present two case studies that exemplify the application of these techniques: a simplified channel equalizer and a wireless LAN receiver.